Hacking work: Critically examining the implications of the new discourse and practices of hacking for work intensification and organisational control. (May 2022) - Bloom, Peter; Śliwa, Martyna
This article discusses the importance of 'hacking work' in organisations, specifically in relation to control over workers in organisations operating within the neoliberal ideological project. Noting the shift in the discourse of hacking beyond references to computer-mediated, anti-establishment oriented activities, we draw on the current meaning of the term 'hacking' that encompasses any 'shortcuts' that can be applied to more efficiently complete tasks. We argue that in workplace contexts, the emergence of 'work hacking' practices can be observed, whereby employees invest time, effort and tacit knowledge into inventing and implementing various 'tricks' in order to fulfil organisational demands while maintaining their own well-being. We discuss how 'hacking work' practices, even if seemingly subversive, present a new form of work intensification and control within the labour process. They can be seen as an exercise in 'working to work' through self-disciplining, aimed at ensuring that the employee completes the allocated tasks regardless of the insufficiency of time and other resources. Their emergence also points to the devaluing of work itself, manifested in a view of work as no more than a set of tasks that need to be 'hacked'.